2016
DOI: 10.1002/anie.201602592
|View full text |Cite
|
Sign up to set email alerts
|

Excavated Cubic Platinum–Tin Alloy Nanocrystals Constructed from Ultrathin Nanosheets with Enhanced Electrocatalytic Activity

Abstract: Excavated polyhedral noble-metal materials that were built by the orderly assembly of ultrathin nanosheets have both large surface areas and well-defined facets, and therefore could be promising candidates for diverse important applications. In this work, excavated cubic Pt-Sn alloy nanocrystals (NCs) with {110} facets were constructed from twelve nanosheets by a simple co-reduction method with the assistance of the surface regulator polyvinylpyrrolidone. The specific surface area of the excavated cubic Pt-Sn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 48 publications
2
76
0
4
Order By: Relevance
“…One approach is to control the surface structure and increase atom utilization efficiency of noble metal NCs in an effort to optimize their catalytic performance while minimizing the usage of noble metal222324252627. The excavated polyhedral NCs, constructed by orderly assembling of ultrathin nanosheets, combine the advantages of both well-defined surfaces and large surface areas, and thus are promising candidates for efficient and low-cost catalysts2829303132. However, formation of the excavated structure is thermodynamically unfavourable during crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…One approach is to control the surface structure and increase atom utilization efficiency of noble metal NCs in an effort to optimize their catalytic performance while minimizing the usage of noble metal222324252627. The excavated polyhedral NCs, constructed by orderly assembling of ultrathin nanosheets, combine the advantages of both well-defined surfaces and large surface areas, and thus are promising candidates for efficient and low-cost catalysts2829303132. However, formation of the excavated structure is thermodynamically unfavourable during crystal growth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the fitting analysis shows the coexistence of Sn 0 and Sn x + in the hollow and solid Pd 2 Sn NPs/P25, where the peaks at 493.3 and 484.4 eV correspond to Sn 0 3d 3/2 and Sn 0 3d 5/2 , and the peaks at 494.7 and 486.2 eV belong to Sn x + 3d 3/2 and Sn x + 3d 5/2 , respectively. Significantly, it revealed that the majority of the surface Sn was presented as Sn x + , and the ratio of Sn x + of the hollow Pd 2 Sn NPs/P25 (85.7%) is higher than that of the solid Pd 2 Sn NPs/P25 (69.4%) . The high ratio of Sn x + is beneficial for improving H 2 O 2 selectivity and reducing H 2 O 2 hydrogenation since the Sn x + modified Pd prefers to block the overhydrogenation of H 2 O 2 .…”
mentioning
confidence: 96%
“…Concave NPs are usually bound with HIFs [35,36]. Xie et al [31] reported the synthesis of excavated cubic Pt-Sn alloy NCs which consist of ultrathin nanosheets with highenergy {110} facets in the presence of PVP. The key factor in the formation of these excavated cubic alloy NCs is that PVP significantly changes the growth kinetics of Pt-Sn alloys.…”
Section: Alloy High-index Faceted Nanocrystalsmentioning
confidence: 99%